Reasons for Dermatology Consultations in Nursing Homes and the Estimated Potential of Teledermatology as a Triage Tool - Frederik M. Klösters; Marieke E.C. van Winden; Freya R. Angenent; Lambertus Henrikus van Bergen; Marjolein van Steveninck-Wensing; Manon C. Zweers; Ann F.S. Galimont-Collen; Ewald M. Bronkhorst; Raymond T.C.M. Koopmans; Satish F.K. Lubeek (Medical Journals Sweden, 2022)
Considering the limited availability of dermatologists to perform live consultations in nursing homes, teledermatology could be used as a triage tool for selection of cases for which live consultations are considered to be of added value compared with teledermatology. This prospective, multicentre observational study aimed to determine the reasons for dermatology consultations in nursing homes and the estimated value of teledermatology as a triage tool, including potential predictors. Skin tumours were the most common reason (n = 161/270; 59.6%) for dermatology consultations in nursing homes. Dermatologists estimated that live consultations added value compared with teledermatology in 67.8% of cases (n = 183). Multivariable logistic regression showed that predictors for this added value of live consultations were: consultations because of a skin tumour; consultations during which a diagnostic or treatment procedure was performed; consultations during which a secondary diagnosis was made; and the dermatologist involved. These results indicate that using teledermatology as a triage tool potentially reduces the need for additional live consultations in one-third of patients, whereas live consultations are estimated to have added value over teledermatology in two-thirds of cases. To make optimal use of the limited capacity for live consultations by dermatologists, it could therefore be helpful if elderly care physicians use teledermatology more frequently.